COPD Clinical Perspectives - Panos, Ralph J. (IntechOpen, 2014)
Chronic Obstructive Pulmonary Disease (COPD) is an increasingly recognized cause of morbidity and mortality. Over the next 10 years, deaths due to COPD are expected to increase by 30% and, by 2030, COPD is estimated to be the third leading cause of death worldwide. Research into the pathophysiology and management of COPD over the past decade has progressed immensely with greater understanding of the global burden of COPD, its pathophysiology, better understanding of the multisystemic manifestations of COPD, and, most importantly, novel and more effective therapeutic strategies. This volume brings together an international group of experts in COPD to provide in depth reviews of clinical perspectives into COPD. Topics range from the diagnosis of airflow limitation by spirometry; distinguishing COPD from another common obstructive lung disease, asthma; alpha-1-antitrypsin deficiency and opportunities to diagnose this most common hereditary cause of COPD and as a paradigm for the development of novel therapeutics; the overlap syndrome - the concurrence of two epidemic disorders: COPD and obstructive sleep apnea; and pulmonary rehabilitation, one of the most effective treatments for COPD.